Prayer, the encounter and participation, the experience: A Pauline exhortation towards a spirituality of prayer - van der Merwe, Dirk G. (Verbum et Ecclesia, 2018)
Numerous references to prayer occur throughout the Old Testament and New Testament. These prayers relate closely to particular circumstances and needs where the petitioner appeals to God, illustrating the importance of prayer as part of the dialogue and communication between God (in the image of a Father) and Israel and the Church (in the image of his children). This article investigates Paul's contribution to this dialogue. In 1 Thessalonians 5:17, Paul exhorts (using the imperative) the Thessalonians to pray 'constantly' (ἀδιαλείπτως), an exhortation located in the last pericope of the epistle, between two other exhortations (imperatives) indicating time ('always') and space ('all circumstances'). Paul thus uses two more exhortations (surrounding the exhortation, 'pray constantly') to define what he means by 'constant' (without ceasing) prayer. His conviction of this necessity leads him to offer himself as an example of 'praying constantly' when he writes to the community in Thessalonica. Prayers in Paul's epistles focus on the existential needs of daily living, to stand firm against evil and the spiritual need to live pure and blameless lives (complete sanctification) until the parousia. Conclusions arising from Pauline textual references on prayer include: the experience of God is not limited to extraordinary events, but subsists essentially in ordinary daily events; the understanding of God's participation in the lives of believers is not always obvious and comprehensible; the Holy Spirit enables believers spiritually to see, hear and understand God's daily involvement in their lives; and, prayer for the believer facilitates spiritual experiences which provide continuous transformation for the one who 'prays without ceasing'. The result, for Paul, of this form of dialogue and communication between God and his Church, is that regular prayer constitutes joy and thankfulness. Intradisciplinary and/or interdisciplinary implications: This research relates to the disciplines of New Testament and Christian Spirituality. The focus is how to experiencing dialogue with the divine regularly every day. A specific mindset is needed to accomplish this; a mindset to see, hear and experience the divine in everyday life in the ordinary events in life.
free
Keywords: BELIEF & doubt; BIBLE. New Testament; BIBLE. Old Testament; CHAPLAINS; CHRISTIAN spirituality; HOLY Spirit; PARTICIPATION; PRAYERS; SPIRITUAL exercises; SPIRITUALITY; THESSALONIKE (Greece)